Dampak Penggunaan Smartphone pada Perilaku Anak Di Desa Muktiharjo Kabupaten Pati - Sri Wulan Endang Saraswati; Deka Setiawan; F. Shoufika Hilyana (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The aims of this study are 1) to analyze the impact of smartphone use on children's behavior in Muktiharjo Village, Pati and 2) to analyze the role of parents in smartphone use in children in Muktiharjo Village, Pati.The research was conducted using a qualitative approach with the type of case study research. The research was conducted in Muktiharjo Village, Margorejo District, Pati Regency. The data collection techniques are through observation, interviews, and documentation. Primary data sources were obtained from observations and interviews with parents and children in Muktiharjo Village. As for the secondary data sources, researchers obtained from supporting documents. Testing the validity of the data used triangulation technique. In this study, triangulation techniques were carried out by combining data received from observations, interviews, and documentation. The data analysis used is qualitative data analysis developed by Miles and Huberman which includes three stages including data reduction, data presentation, verification or conclusion.The results of the study indicate that the role of parents is very important in reducing the impact of smartphone use on children and children's behavior can be controlled. Behavioral disorders in children include emotional behavior, social behavior, and lazy behavior.